Oxford handbook of the indian constitution/ edited by Sujit Choudhary, Madhav Khosla and Pratap Bhanu Mehta - Choudhry, Sujit (ed.); Khosla, Madhav (ed.); Mehta, Pratap Bhanu (ed.) (New Delhi, 2016)
The Oxford Handbook of the Indian Constitution is a wide-ranging, analytical reflection on the major themes and debates that surround India's Constitution. The Handbook provides a comprehensive account of the developments and doctrinal features of India's Constitution, as well as articulating frameworks and methodological approaches through which studies of Indian constitutionalism and constitutionalism more generally, might proceed. Its contributions range from rigorous, legal studies of provisions within the text to reflections upon historical trends and social practices. As such the Handbook is an essential reference point not merely for Indian and comparative constitutional scholars, but for students of Indian democracy more generally.
Keywords: Constitutional law -- India